2004
DOI: 10.1107/s1600536804033598
|View full text |Cite
|
Sign up to set email alerts
|

A pseudopolymorph of valdecoxib

Abstract: Key indicatorsSingle-crystal X-ray study T = 173 K Mean '(C±C) = 0.003 A Ê Disorder in solvent or counterion R factor = 0.044 wR factor = 0.131 Data-to-parameter ratio = 14.6For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The stacking of molecules along the c -axis of 1 - 107 and along the a -axis of 1 - 112 (SC B ) is repeated in methyl 4-aminobenzoate 45 ( 2-II ), dimethyl terephthalate 46 ( 3 ), methyl 4-bromobenzoate 47 ( 4 ) and its iodo 47 ( 5 ) and ethynyl 48 ( 6 ) analogues, methyl 4-(bromomethyl)benzoate 49 ( 7 ) and methyl 4-methylbenzoate 50 ( 8 ). Form 1 - 112 is even 2D similar (SC C) with polymorph 2-II of 4-aminobenzoate, 45 with which it shares a centrosymmetric double layer consisting of two layers of H-bonded chains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stacking of molecules along the c -axis of 1 - 107 and along the a -axis of 1 - 112 (SC B ) is repeated in methyl 4-aminobenzoate 45 ( 2-II ), dimethyl terephthalate 46 ( 3 ), methyl 4-bromobenzoate 47 ( 4 ) and its iodo 47 ( 5 ) and ethynyl 48 ( 6 ) analogues, methyl 4-(bromomethyl)benzoate 49 ( 7 ) and methyl 4-methylbenzoate 50 ( 8 ). Form 1 - 112 is even 2D similar (SC C) with polymorph 2-II of 4-aminobenzoate, 45 with which it shares a centrosymmetric double layer consisting of two layers of H-bonded chains.…”
Section: Resultsmentioning
confidence: 99%
“…The stacking of molecules along the c-axis of 1-107 and along the a-axis of 1-112 (SC B) is repeated in methyl 4-aminobenzoate 45 (2-II), dimethyl terephthalate 46 (3), methyl 4-bromobenzoate 47 (4) and its iodo 47 (5) and ethynyl 48 4; (e) alternative representation of the same sequence, highlighting molecule types 1 (green), 2 (gray), and 3 (pink). H), but here the separation between adjacent molecular centroids is substantially increased by 0.5 Å. SC H is also present in three polymorphs of ethyl 4-aminobenzoate 52 (10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Like any other COX-2 selective inhibitor, etoricoxib selectively inhibits isoform 2 of the enzyme cyclo-oxigenase (COX-2). The crystal structure of valdecoxib, a non-steroidal antiinflammatory drug (Malathy Sony et al, 2005), a pseudopolymorph of valdecoxib (Yathirajan et al, 2005) and celecoxib, a COX-II inhibitor (Vasu Dev et al, 1999) have been reported. In the view of the importance of etoricoxib, this paper presents the crystal structure of the title compound, etoricoxib picrate.…”
Section: Methodsmentioning
confidence: 99%
“…For background to coxibs, traditional non-steroidal anti-inflammatory drugs, see: Rimon et al (2010); Shriner et al (1980); Patrignani et al (2003). For related structures, see: Malathy Sony et al (2005);Vasu Dev et al (1999); Yathirajan et al (2005). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…A solvatomorph of valdecoxib has been reported, where the unit cell contains half a molecule of ethyl methyl ketone in the asymmetric unit 123. The crystal packing is stabilized by NH···O hydrogen bonds, and the conformation of the compound is similar to that of the nonsolvated orthorhombic crystal form.…”
Section: Structural Characterization and Properties Of Polymorphs Andmentioning
confidence: 99%